Influential mapping of SDG disclosures based on innovation and knowledge using an integrated decision-making approach - Hasan Dinçer; Ahmad El-Assadi; Mohsen M. Saad; Serhat Yüksel (Journal of Innovation & Knowledge (JIK), 2024)
This study addresses the challenges faced by organizations in prioritizing sustainability reporting aligned with the United Nations' Sustainable Development Goals (SDGs). We examine the cause-and-effect relationships among sustainability dimension-related disclosures and specific SDG criteria. This study advocates a prioritization approach to sustainability reporting across sustainability dimensions and SDG reporting criteria. To conduct our empirical analysis, we designate SDG13 (Climate Change), SDG7 (Affordable and Clean Energy), and SDG12 (Responsible Consumption and Production) as representatives of the sustainability dimensions related to the biosphere, society, and economy, respectively. We employ a novel methodology that integrates quantum spherical fuzzy sets (QSFS) into the decision-making trial and evaluation laboratory (DEMATEL) technique. We demonstrate the superiority of our methodology, which enhances the precision of decision-making under uncertainty. Our findings reveal that biosphere disclosure influences the disclosure of the remaining dimensions. Notably, we find that the disclosure criteria for each SDG are interrelated and can be ranked according to the intensity of their influence on each other. Disclosure of 'materiality analysis for sustainable energy' is the most influential factor. These findings have managerial implications for future studies. By identifying the interrelations among disclosure criteria and prioritizing the most influential factors, companies can focus their efforts on the most impactful aspects. Our findings provide organizations with a foundation for developing an innovative reporting framework with a prioritization approach to sustainability disclosures. Policymakers can leverage these insights to enhance current reporting practices and contribute to broader discourse on sustainable development.
Keywords: D81; Q40; Q53; Q54; Q56; 650; Sustainability dimensions; Sustainability development goals; Disclosure criteria; DEMATEL; QSFS